Are High Carbon Stocks in Agroforests and Forest Associated with High Plant Species Diversity? - Natalia, Depi; Arisoesilaningsih, Endang; Hairiah, Kurniatun (AGRIVITA, Journal of Agricultural Science, 2017)
Conserving plant diversity and retaining terrestrial carbon stocks are targets for environmental policy and appear to be generally compatible. However, detailed information on the way both respond to agroforestry management is lacking. Rubber and fruit tree agroforestry systems combine planted trees and trees that are tolerated or actively managed that derived from natural vegetation. The research aimed to evaluate plant species diversity, vegetation structure, and C stock in rubber agroforestry system (AF) and secondary forest grown in silty clay and sandy soils in Pulang Pisau Regency, Central Kalimantan province. A number of multistrata agroforestry systems was compared to the secondary (natural) forests (SNF) of the area; these included Fruit-Based Rubber Agroforestry (AFB) of about 100 years of age, Old Rubber Agroforestry (ARO) and Young Rubber Agroforestry (ARY). The highest C stock was found in AFB (415 Mg ha-1), while the average C stocks of other AF and SNF were 217 Mg ha-1. A plant diversity index (H’) was only weakly correlated to aboveground C stocks. Including the farmer-managed agroforests in schemes to reduce emissions from deforestation and forest degradation is relevant, as their carbon stocks match or exceed those of remaining forests in the area.